Traumatic and overuse injuries among international elite junior rowers - Smoljanovic, T.; Bojanic, I.; Hannafin, J. A.; Hren, D.; Delimar, D.; Pecina, M. (The American Journal of Sports Medicine, 2009)
Background Junior rowers have competed internationally for over 4 decades, and there are no epidemiological data available on traumatic and overuse injury in this population.